Urban Mobility in Eastern Poland : The Way Forward - World Bank (Washington, DC, 2015)
In the second half of 2013, the World Bank secured grant funding from the Korea Green Growth Partnership for analytical support and technical assistance related to sustainable urban transport systems in select cities in Eastern Poland. Established in 2011, the Korea Green Growth Partnership strengthens cooperation between the Government of Korea and the World Bank Group to help countries achieve sustainable and inclusive development by developing and sharing practical knowledge around innovative green growth solutions. The objective of the first phase of this technical assistance involved assessing the urban transport sector in the selected cities, Bialystok, Lublin, Olsztyn, and Rzeszow, with a primary focus on public transportation and the aim of identifying areas for improvement. The second phase of this technical assistance will focus on areas identified in the first phase, subject to agreement from the participating cities, as well as capacity building activities. This report provides a set of recommendations related to the legal and institutional framework for urban transport in Poland; summarizes the assessment of urban mobility for Bialystok, Lublin, Olsztyn, and Rzeszow; and assesses the framework for inter-municipal coordination in Poland.